2024
DOI: 10.1097/cin.0000000000001132
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Experiences of Empathy in a Virtual Reality Simulation Game

Katri Mattsson,
Elina Haavisto,
Satu Jumisko-Pyykkö
et al.

Abstract: Empathy is significant in nursing, and showing empathy toward a patient positively impacts a patient's health. Learning empathy through immersive simulations is effective. Immersion is an essential factor in virtual reality. This study aimed to describe nursing students' experiences of empathy in a virtual reality simulation game. Data were collected from nursing students (n = 20) from May 2021 to January 2022. Data collection included individual semistructured interviews; before the interviews, the virtual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 38 publications
5
6
0
Order By: Relevance
“…Experiential learning has shown good results in increasing empathy [14] since it focuses on learning through lived or shared experience, and it has been utilized using simulations, role-playing games, and virtual reality (VR) in teaching [5], [10], [14], [15]. A recent systematic review revealed that the application of different modalities of simulation promotes empathy in nursing education [16], while another systematic review demonstrated that for improving empathy, the most effective interventions were immersive and experiential simulations providing opportunities for reflection [17].…”
Section: Virtual Reality In Empathy Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiential learning has shown good results in increasing empathy [14] since it focuses on learning through lived or shared experience, and it has been utilized using simulations, role-playing games, and virtual reality (VR) in teaching [5], [10], [14], [15]. A recent systematic review revealed that the application of different modalities of simulation promotes empathy in nursing education [16], while another systematic review demonstrated that for improving empathy, the most effective interventions were immersive and experiential simulations providing opportunities for reflection [17].…”
Section: Virtual Reality In Empathy Educationmentioning
confidence: 99%
“…Simulation experiences can reduce the decline in experiencing empathy during training because it gives the student a sense of control and helps identifying professional behavior in patient relationships [18]. In VR simulations, students have been more in the role of a patient [5], [10], [19], [20] than a nurse [15]. Research has shown that the most effective simulation exercises for learning empathy are those in which the learner takes on the role of a patient [18].…”
Section: Virtual Reality In Empathy Educationmentioning
confidence: 99%
See 3 more Smart Citations